(3GdOQ GdfajS ajeG RGO Ydi LfGf GdLfGS hCLfGS GdJLfjSs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3GdHGH GdKGfi ai MOg hQSeg s
(3BNQgG (B:s
(3ajchf Pdc SHHkG ddWYf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs